2014
DOI: 10.1016/j.nbd.2014.05.038
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell-derived motor neurons from spinal and bulbar muscular atrophy patients

Abstract: Spinal and bulbar muscular atrophy (SBMA, Kennedy’s disease), is a motor neuron disease caused by polyglutamine repeat expansion in the androgen receptor. Although degeneration occurs in the spinal cord and muscle, the exact mechanism is not clear. Induced pluripotent stem cells from spinal and bulbar muscular atrophy patients provide a useful model for understanding the disease mechanism and designing effective therapy. Stem cells were generated from six patients and compared to control lines from three healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 33 publications
3
48
0
Order By: Relevance
“…Mature neurons were derived from iPSC (Supplementary Figure S5C) and confirmation of neuronal phenotypes was achieved through expression of sequential markers of differentiation: iPSCs expressed TRA-1-81 demonstrating pluripotency (Supplementary Figure S5D); neural stem cells (NSC) expressed Nestin and Sox1 (Supplementary Figure S5E); and neurons expressed neuronal nuclei marker (NeuN) (Supplementary Figure S5F). Motor neurons, a mature neuronal subtype that is primarily lost in ALS, were also derived from iPSC 49 and their differentiation was confirmed by expression of non-phosphorylated neurofilament marker, SMI-32 (Supplementary Figure S5G).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Mature neurons were derived from iPSC (Supplementary Figure S5C) and confirmation of neuronal phenotypes was achieved through expression of sequential markers of differentiation: iPSCs expressed TRA-1-81 demonstrating pluripotency (Supplementary Figure S5D); neural stem cells (NSC) expressed Nestin and Sox1 (Supplementary Figure S5E); and neurons expressed neuronal nuclei marker (NeuN) (Supplementary Figure S5F). Motor neurons, a mature neuronal subtype that is primarily lost in ALS, were also derived from iPSC 49 and their differentiation was confirmed by expression of non-phosphorylated neurofilament marker, SMI-32 (Supplementary Figure S5G).…”
Section: Resultsmentioning
confidence: 97%
“…Although both AD and ALS are associated with increased cellular senescence, qRT-PCR using brain tissue RNA samples showed that SASP cytokine IL-6 and a p53-inducible senescence Figure 5 Increased neuronal death upon co-culture with Δ133p53-knocked-down or p53β-overexpressing astrocytes. Early-passage primary astrocytes (P5) with Δ133p53 siRNA and control siRNA (generated as in Supplementary Figure S3) (a, b, e, and f) and those with p53β -overexpression or control vector (generated as in Supplementary Figure S4) (c, d, g, and h) were used in co-culture for 48 h with motor neurons 49 or less specialized neurons (as generated as in Supplementary Figures S5C-F Data are presented as mean ± S.E.M. NS indicates P40.05, *P ≤ 0.05, **P ≤ 0.01, ***P ≤ 0.001 by unpaired two-tailed Student's t test p53 isoforms in neurodegeneration C Turnquist et al regulator p21 WAF1 were upregulated more remarkably in ALS, while NOS2 upregulation was more evident in AD (Figure 7c), possibly reflecting the different disease pathologies.…”
Section: Resultsmentioning
confidence: 99%
“…Fibroblasts were stained on coverslips as previously described 14. Antibodies used for staining can be found in Table S2.…”
Section: Methodsmentioning
confidence: 99%
“…Instability can be particularly troubling when reprogramming patient samples from diseases, such as HD, spinal-bulbar muscular dystrophy, C9ORF72-associated ALS, and FTD, that are caused by expansion of repeat regions within the disease-causing gene (Table 1). In these lines, the repeat region is often not stable during and after reprogramming, and the instability can continue during differentiation (85, 86). For example, in one study, six iPSC lines with spinal-bulbar muscular atrophy were derived, but only three were used in which the disease associated poly-Q-androgen receptor expansion was stable over multiple passages (86).…”
Section: Limitations Of Ipsc Technologymentioning
confidence: 99%